Forecast revisions of Mexican inflation and GDP growth - Carlos Capistrán; Gabriel López-Moctezuma (Banco de México, 2010)
We analyze forecasts of inflation and GDP growth contained in Banco de México's Survey of Professional Forecasters for the period 1995-2009. The forecasts are for the current and the following year, comprising an unbalanced three-dimensional panel with multiple individual forecasters, target years, and forecast horizons. The fixed-event nature of the forecasts enables us to examine efficiency by looking at the revision process. The panel structure allows us to control for aggregate shocks and to construct a measure of the news that impacted expectations in the period under study. The results suggest that respondents seem to rely for longer than appears to be optimal on their previous forecasts, and that they do not seem to use past information in an efficient manner. In turn, this means there are areas of opportunity to improve the accuracy of the forecasts, for instance, by taking into account the positive autocorrelation found in forecast revisions.
Keywords: C23; C53; C83; E37; 330; Evaluating forecasts; Inflation forecasting; Macroeconomic forecasting; Panel data; Surveys; Inflation; Prognose; Sozialprodukt; Wirtschaftsprognose; Mexiko